Mine haul road maintenance management systems - Thompson, Roger; Visser, A. (SAIMM, 2003)
In surface mining operations, ultra-heavy trucks operate on haul road networks which are typically from 10-40km in length. These road networks are often not optimally designed and maintained and as a result, identifying and remediating road functional defects is problematic. Most surface mine operators agree good roads are desirable, but find it difficult to translate this into an effective road maintenance system. This paper presents a haul road maintenance management system which utilises an assessment of rolling resistance based on a functional performance evaluation of a haul road, together with mine haul truck operating cost models to derive the optimal frequency of road maintenance. A typical application is presented which illustrates the potential of the technique to manage maintenance as and where needed with resultant reduction in total road user costs and an improvement in service provided for the road user.